2016
DOI: 10.1186/s41235-016-0009-4
|View full text |Cite
|
Sign up to set email alerts
|

Men’s perceptions of women’s sexual interest: Effects of environmental context, sexual attitudes, and women’s characteristics

Abstract: Men’s perceptions of women’s sexual interest were studied in a sample of 250 male undergraduates, who rated 173 full-body photos of women differing in expressed cues of sexual interest, attractiveness, provocativeness of dress, and the social-environmental context into which the woman’s photo had been embedded. Environmental context significantly influenced men’s judgments of sexual interest, independently of the affective cues of sexual interest themselves and of provocativeness of dress and attractiveness. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…It is easy to imagine how risk‐linked operation of all three processes might increase the likelihood of subsequent coercive or aggressive behavior: Decreased sensitivity might make it more difficult to distinguish a woman's later consent and non‐consent cues, a higher baseline justifiability might encourage more rapid and intimate sexual advances, and a more liberal bias might delay recognition of and appropriate responses to a woman's declining interest. Importantly, the current findings, although based on responses to a 21‐item questionnaire, are consistent with prior performance‐based work documenting a role for sexual misperception in sexual coercion and aggression (Farris et al, , ; Treat, Farris et al, ; Treat et al, ; Treat, Hinkel, Smith, & Viken, ; Treat, Viken, Farris, & Smith, ). In particular, sexual‐aggression risk in the current study is associated with both decreased sensitivity and a potentially maladaptive bias.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It is easy to imagine how risk‐linked operation of all three processes might increase the likelihood of subsequent coercive or aggressive behavior: Decreased sensitivity might make it more difficult to distinguish a woman's later consent and non‐consent cues, a higher baseline justifiability might encourage more rapid and intimate sexual advances, and a more liberal bias might delay recognition of and appropriate responses to a woman's declining interest. Importantly, the current findings, although based on responses to a 21‐item questionnaire, are consistent with prior performance‐based work documenting a role for sexual misperception in sexual coercion and aggression (Farris et al, , ; Treat, Farris et al, ; Treat et al, ; Treat, Hinkel, Smith, & Viken, ; Treat, Viken, Farris, & Smith, ). In particular, sexual‐aggression risk in the current study is associated with both decreased sensitivity and a potentially maladaptive bias.…”
Section: Discussionsupporting
confidence: 89%
“…A sharper decline in justifiability ratings across items indicates higher sensitivity , whereas a more gradual decline indicates lower sensitivity . We expected that higher‐risk men would show lower sensitivity , consistent with prior performance‐based findings (Farris et al, , ; Treat, Farris et al, ; Treat et al, ; Treat, Hinkel, Smith, & Viken, ; Treat, Viken, Farris, & Smith, ). Figure illustrates higher‐risk men's more gradual reduction in justifiability ratings than lower‐risk men.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Finally, this work has a number of implications for understanding risk behaviors and sexual health. For example, female provocativeness of dress is a cue hypothesized to be misperceived by men as indicative of a woman's sexual interest (Treat, Hinkel, Smith, & Viken, 2016). Indeed, several studies have shown a link between rape supportive attitudes as well as sexual aggression perpetration and reliance on a woman's POD, rather than her affect (Treat, Church, & Viken, 2017).…”
Section: Future Directionsmentioning
confidence: 99%